An Analysis of the Effect of Academic Stress on Achievement Motivation among Senior-Secondary Students of Mathura District (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this study is to identify and examine the impact of stress on the achievement motivation of the senior secondary students. The Achievement motivation is a phenomenon of consistently attempting for success and to select target oriented success or failure activities. In the present era, a very high motivation for achievement has become very vital need for the students especially in terms of seeking admission into esteemed or reputed colleges in higher education or to become highly successful in life. The word ‘Stress’ is generally used to describe the feeling of not being able to manage with the things or fatigue or an unwanted pressure. The term stress in this study implies the strain, the inability or the hardship among the senior secondary students. Several studies in this field have revealed that the students are very often exposed to stress and strains which can in-turn have very severe negative impacts on their work, health, life and overall well-being. In order to complete the present study, the researcher has selected a total of 120 senior-secondary students (60 Boys & 60 Girls) randomly from three different schools located in Mathura district. The SPSS package (v-16.0) for undertaking “One way analysis of Variance”, post hoc test and t-test have been utilized to analyse the data. The findings of the present study signify that a moderate level of stress group has a better achievement motivation as compared to the high level and low levels of stress groups. While it is also observed that there exists no relevant difference between the genders (Boys & Girls) and it is also revealed that the girl students have comparatively better achievement motivation than the boy students at senior-secondary level.